Targeting CD300a Signaling With a Phosphatidylserine‐Presenting Hydrogel Rescues Macrophage Dysfunction and Accelerates Diabetic Wound Healing - Lele Wu; Xuetong Hao; Yang Zou; Xinglin Chen; Junyan Kong; Chunning Gu; Wenjie Ma; Zhongjun Yang; Huifen Liu; Mengmeng Liu; Xin Tong (Advanced Healthcare Materials, 2026)
ABSTRACT The delayed healing of diabetic wounds involves both impaired efferocytosis and dysfunctional phosphatidylserine (PS) receptor signaling, leading to macrophage defects in migration, persistent M1 polarization, and diminished cellular resilience. To address this multifaceted pathology, a bioactive wound dressing was developed by incorporating PEGylated RGD‐grafted phosphatidylserine liposomes (PEG/RGD‐PSLs) into a photocrosslinkable hyaluronic acid methacryloyl (HAMA) hydrogel matrix. This platform provides sustained, delivery of a biomimetic “eat‐me” signal while actively reprogramming macrophage behavior. Under diabetic‐mimicking stress conditions, PEG/RGD‐PSLs significantly enhanced macrophage migration, promoted M1‐to‐M2 phenotypic transition, and conferred robust cytoprotection by preserving mitochondrial integrity, attenuating oxidative stress, and suppressing pathological extracellular vesicle release. Mechanistically, PS binding upregulated the inhibitory receptor CD300a, which suppressed the MyD88/NF‐κB pathway and downregulated pro‐inflammatory genes. Critically, siRNA‐mediated CD300a knockdown abolished these anti‐inflammatory and NF‐κB‐suppressive effects, establishing CD300a as necessary for therapeutic action. In a diabetic rat model, a single application of the bioactive hydrogel significantly accelerated wound closure, stimulated angiogenesis, improved organized collagen deposition, and actively shifted the wound immune microenvironment toward a pro‐reparative M2‐dominant state. Collectively, this study identifies the PS/CD300a/NF‐κB axis as a key regulatory node for rescuing macrophage dysfunction and establishes a functionally active hydrogel‐based therapy for chronic diabetic wounds.